Inflation scares and bond market signals: Is the Fed's policy action asymmetric? - Luca Agnello (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
This paper is concerned with the question whether, over the last two decades, the priority to maintain the credibility as inflation 'fighter' induced the Fed to conduct a monetary policy that can be considered asymmetric in nature. Considering that the longer-term bond interest rate is the most reliable indicator used to gauge Fed's credibility to low inflation, we investigate the equilibrium-type relationship between the monetary policy instrument, the Federal Funds rate, and 10-year government bond rate within a threshold-cointegration framework in a similar fashion of Enders and Siklos (2001). Our empirical findings indicate that, during the period 1980-2005, both the direction and magnitude of changes in long-term expected inflation, reflected in 10-year bond rate movements, influenced the timing of the Fed's action. Therefore, we conclude that asymmetries in the term-spread dynamics are the result of the Fed's behaviour that can be considered representative of a monetary policy essentially asymmetric.
Keywords: 330